The Soundtrack of Revolution Memory, Affect, and the Power of Protest Songs - Rosenberg, Tiina (My University, 2013)
All cultural representations in the form of songs, pictures, literature, theater, film, television shows, and other media are deeply emotional and ideological, often difficult to define or analyze. Emotions are embedded as a cultural and social soundtrack of memories and minds, whether we like it or not. Feminist scholarship has emphasized over the past decade that affects and emotions are a foundation of human interaction. The cognitive understanding of the world has been replaced by a critical analysis in which questions about emotions and how we relate to the world as human beings is central (Ahmed 2004: 5-12). It is in this memory-related instance that this article discusses the unexpected reappearance of a long forgotten song, Hasta siempre, as a part of my personal musical memory. It is a personal reflection on the complex interaction between memory, affect and the genre of protest songs as experiences in life and music. What does it mean when a melody intrudes in the middle of unrelated thoughts, when one’s mind is occupied with rational and purposive considerations? These memories are no coincidences, I argue, they are our forgotten selves singing to us.
Keywords: 306 Kultur und Institutionen; music; memory; affect; emotion; feminism; gender; kitsch; solidarity